A combined molecular dynamics simulation and DFT study on mercapto-benzamide inhibitors for the HIV NCp7 protein. Issue 41 (18th October 2022) - Cardia, R.; Cappellini, G.; Valentini, M.; Pieroni, E.
Abstract : Molecular dynamics and quantum simulations are performed to elucidate some aspects of the action mechanism of mercapto-benzamides, a proposed class of antivirals against HIV-1. Abstract : Molecular dynamics and quantum simulations are performed to elucidate some aspects of the action mechanism of mercapto-benzamides, a proposed class of antivirals against HIV-1. These molecules act as prodrugs that, after modifications in the biological environment, are able to denature the HIV nucleocapsid protein 7, a metal binder protein, with two zinc finger motifs, vital for RNA maturation and viral replication. Despite their attractive features, these molecules and their biological target are not well understood. Simulations were performed to support a proposed action mechanism, based on the activation of mercapto-benzamides by acetylation, targeting a relatively rare protein hydrolyzed state, followed by trans -molecular acetylation from the molecule to the protein and finally the direct interaction of the molecular sulphur atom of mercapto-benzamides with the zinc atom coordinated by the protein. Our simulation results are in agreement with the NMR data about the zinc finger binding protein equilibrium configurations.